The Round Towers of the Andalusi-Catalan Borders (8th–10th centuries) - Martí, Ramon; Viladrich, Mª Mercè (Journal of Islamic Archaeology, 2021)
This article reviews the subject of early medieval fortifications in Catalonia. In particular, we focus on the free-standing round towers, a type of construction that presents many variants. Academic disputes abound as to their origins; some of them are ascribed to the Roman period, whereas others are thought to belong to the time of the Catalan Counts (from the middle of the 10th century until the middle of the 12th century). These towers are common in wide areas of al-Andalus, where their Islamic origin is usually not disputed. Here, we explore the oldest samples found in the territories of Catalonia, by cross-checking archaeological and monumental data with textual sources, in order to test the hypothesis of an Andalusi origin of these very early constructions. This study covers a large geographical area, more than 300 km straight along the Catalan coastline and neighbouring territories. On this stretch of land there were as many as three different frontiers in the period under study between the lands under Christian or Islamic rule. We discuss up to 50 towers, each one built with the purpose of surveillance and control of the territory. This mission reflects a strategy of defence, which makes sense in the Islamic era if the enemy is coming from the north. Furthermore, the successive borders are linked to different styles of towers, which show the transformation from the 8th to the 10th centuries. We identify some of their builders among the Arab governors of the period. Initially relatively low buildings, these towers took on a notably monumental character in the days of Sulayman al-A'rabi. During the 9th century, the Carolingian intrusions sparked a rapid change, with the construction of much higher towers with battlements on the roofs, such as the ones that are predominant in the area around the city of Tortosa at the beginning of the 10th century.